TREN PENELITIAN AUDIT INTERNAL GLOBAL: ANALISIS BIBLIOMETRIK SCOPUS 2020–2025 - Kalmet Nehru; Fitriana Dachlan; Rachmat Agus Santoso (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2026)
This study aims to analyze the development of internal audit research publications during 2020–2025, identify collaboration patterns among authors, countries, and keywords, examine the evolution of research themes through trend topics and thematic maps, and identify the most globally cited documents in global internal audit research. The study employs a bibliometric literature review approach using Biblioshiny software. Research data were obtained from the Scopus database through a systematic screening process using the keyword “internal audit,” limited to the Business, Management and Accounting subject area, article document type, and English-language publications, resulting in 488 scientific articles as the research sample. The findings indicate that internal audit research publications experienced relatively stable growth with an annual growth rate of 5.79%. Internal audit research strongly developed around themes such as corporate governance, risk management, internal control, and internal audit function. In addition, emerging topics including artificial intelligence, cybersecurity, and continuous auditing have begun to appear as new directions in internal audit research. The most influential articles were dominated by studies discussing digital transformation, corporate governance, organizational sustainability, and audit quality. This study provides a systematic overview of the development direction of global internal audit research based on Scopus metadata using Biblioshiny.